Effect of Using Different Levels of Energy in Pre-Starter Diets of Broiler Chicks on Performance (Journal of Hama University, 2019)
An experiment was carried out using 150 unsexed chicks of a commercial broiler breed taken randomly from a hatchery after the start of hatching. The chicks were distributed into three groups of 50 chicks each. The chicks were fed a certain type of mash feed for 7 days as follows:The chicks of the1st group were given the basal Pre-Starter diet directly after hatching having 3200k.cal/kg Metabolisable Energy (ME), according to the American feed tables of (NRC, 1994).   The 2nd and the 3rd group of chicks were given the Pre-Starter diet directly after hatching but having ME=3100 k.cal/kg, ME=3000k.cal/kg respectively, and maintaining the rest of the nutrients as in the basal diet.  After 7 days, the chicks of three groups fed a broiler pellet commercial diet until the age of 42 days.The results showed the importance of ME=3200k.cal/kg in the diet directly after hatching on the average live weight at the end of the first week, the differences were significant (P ≤ 0.01) between the chicks of the first group compared to chicks of the second and the third group. No significant differences were noticed among the average live weight of the chicks of all groups at the end of the experiment.It was showed that ME=3200k.cal/kg in the diet directly after hatching improved feed conversion ratio (1.69) compared to birds of the groups at the end of the experiment.